Strategi Pengembangan Usaha Micro Kecil Menengah (UMKM) Kopi Gunung Brojo di Desa Sumber Purwantoro - Ma'rufah, Afni; Lutfia, Fadila Ayu; Laily, Fadila Nur; Amalia, Nisa Wahyu (Abdimas Indonesian Journal, 2024)
In this community service activity there is a problem, namely the lack of competent human resources in utilizing qualified natural products. Therefore, the existence of UMKM is a business developed by individuals in Sumber Village which aims to increase people's purchasing power for a product. The product is kopt. Where coffe is a micro, small and medium enterprise (UMKM) in the Desa Sumber, Parwantoro, Wonogiri. The Gunung Beojo coffee business was pioneered by Deddy Kusuma Endranto, a resident of Galih dem Sumber, which is the hallmark of the Stumber Village kops, namely zobusta, which was later named Kopi Gummg Brojo the method the author chose is to use the ABCD method which prioritizes the use of assets and potential that exist around the service and damlik areas by one of the communities. The community in question is the people in Sumber Village who have micro, small and medium enterprises specifically for the owners of UMKM Guming Brojo Coffee. conduct training for local residents on how to properly map coffee, procedures for making ground coffee and how to properly taste coffee. The aim is not to develop individuals, in terms of increasing the knowledge, skills possessed, and attitudes of these individuals